Pro HTML5 Programming Powerful APIs for Richer Internet Application Development - Lubbers, Peter; Albers, Brian; Salim, Frank; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
HTML5 is here, and with it, web applications take on a power, ease, scalability, and responsiveness like never before. In this book, developers will learn how to use the latest cutting-edge HTML5 web technology$1 (Bavailable in the most recent versions of modern browsers$1 (Bto build web applications with unparalleled functionality, speed, and responsiveness. Explains how to create real-time HTML5 applications that tap the full potential of modern browsers Provides practical, real-world examples of HTML5 features in action Shows which HTML5 features are supported in current browsers Covers all the new HTML5 APIs to get you up to speed quickly with HTML5s
Keywords: Computer science; Computer Science; Programming Techniques